A Humanistic Approach in Thematic Learning of The Merdeka Curriculum - Nursya'bani, Kinkin Karimah; Herlambang, Yusuf Tri (International Conference on Elementary Education, 2025)
This study aims to examine the implementation and theoretical foundation of the humanistic approach in thematic learning under the Curriculum Merdeka at Mutiara Bunda Elementary School in Bandung. A qualitative case study method was employed, gathering in-depth data through participatory observation, interviews, and documentation (Creswell, 2016; Yin, 2019). The findings indicate that the implementation is comprehensive and consistently grounded in Carl Rogers' Three Facilitative Conditions (Empathy, Congruence, and Unconditional Positive Regard), effectively creating a psychologically safe classroom environment necessary for student growth (Rogers, 1969; Maslow, 1970). Teachers prioritize open and authentic interactions, transforming their role into that of an empathetic facilitator (Dinata, 2020; Holisah, 2022). Learning evaluation is performed holistically and formatively through personal reflection and learning journals, placing emphasis on the student's internal frame of reference and self-concept development (Rogers, 1969). The main challenge is the systemic conflict between the personalized demands of humanistic pedagogy and the heavy administrative and time pressures within the current educational structure. This study provides a significant empirical contribution by positioning the humanistic approach as the essential philosophical foundation required for achieving the holistic goals and character development outlined in the Profil Pelajar Pancasila (Mulyanto, Arfanti, & Damiati, 2024).